Capnocytophaga canimorsus Septicemia With Sepsis-Induced Coagulopathy and Endocarditis - Jeannine L. Kühnle; Maximilian Leitner; Vitalie Mazuru; Kai Borchardt; Sören L. Becker; Franziska Roth; Robert Bals; Philipp M. Lepper; Hans-Joachim Schäfers; Isabella T. Jaumann (Case Reports in Infectious Diseases)
Capnocytophaga canimorsus is a rare cause of serious infections with a high mortality of 10% to 30%. It is usually found in the oral cavity of cats and dogs and can cause severe sepsis in immunocompromised patients. An 81-year-old female Caucasian patient presented with C. canimorsus sepsis after a dog bite in her finger three days before presentation to our emergency department. She initially was presented to us with sepsis, thrombopenia, and schistocytes in her laboratory findings, suggesting the differential diagnoses of the multiple subtypes of thrombotic microangiopathy. She was admitted to the medical intensive care unit of the University Hospital of Saarland because of septic shock with circulatory insufficiency. The patient received plasmapheresis, antibiotics, and dialysis, under which she improved significantly. The fingertip of the affected finger developed necrosis and had to be amputated. Furthermore, the patient was diagnosed with a mitral valve endocarditis, a very rare complication of C. canimorsus infection. It was treated conservatively with antibiotics and was no longer detectable 8 weeks after the diagnosis. Surgical intervention was not needed. The case describes well that it is still difficult to distinguish between thrombotic thrombocytopenic purpura (TTP), disseminated intravascular coagulation (DIC), and sepsis-induced coagulopathy (SIC), especially in the early phases of acute disease, especially in C. canimorsus-induced sepsis.